Perennial Flooding in the Accra Metropolis: the Human Factor - Adams, Augustine Ganiyu (2011)
A Thesis submitted to the School Of Graduate Studies. Kwame Nkrumah University of Science and Technology in Partial fulfilment of the requirements for the Degree of Master of Science in Development Planning and Management, 2008